Appropriate referral and selection of patients with chronic pain for spinal cord stimulation: European consensus recommendations and e‐health tool. (4th April 2020) - Thomson, Simon; Huygen, Frank; Prangnell, Simon; De Andrés, José; Baranidharan, Ganesan; Belaïd, Hayat; Berry, Neil; Billet, Bart; Cooil, Jan; De Carolis, Giuliano; Demartini, Laura; Eldabe, Sam; et al.
Abstract: Background: Spinal cord stimulation (SCS) is an established treatment for chronic neuropathic, neuropathic‐like and ischaemic pain. However, the heterogeneity of patients in daily clinical practice makes it often challenging to determine which patients are eligible for this treatment, resulting in undesirable practice variations. This study aimed to establish patient‐specific recommendations for referral and selection of SCS in chronic pain. Methods: A multidisciplinary European panel used the RAND/UCLA Appropriateness Method (RUAM) to assess the appropriateness of (referral for) SCS for 386 clinical scenarios in four pain areas: chronic low back pain and/or leg pain, complex regional pain syndrome, neuropathic pain syndromes and ischaemic pain syndromes. In addition, the panel identified a set of psychosocial factors that are relevant to the decision for SCS treatment. Results: Appropriateness of SCS was strongly determined by the neuropathic or neuropathic‐like pain component, location and spread of pain, anatomic abnormalities and previous response to therapies targeting pain processing (e.g. nerve block). Psychosocial factors considered relevant for SCS selection were as follows: lack of engagement, dysfunctional coping, unrealistic expectations, inadequate daily activity level, problematic social support, secondary gain, psychological distress and unwillingness to reduce high‐dose opioids. An educational e‐health tool was developed that combines clinical and psychosocial factors into an advice on referral/selection for SCS. Conclusions: The RUAM was useful to establish a consensus on patient‐specific criteria for referral/selection for SCS in chronic pain. The e‐health tool may help physicians learn to apply an integrated approach of clinical and psychosocial factors. Significance: Determining the eligibility of SCS in patients with chronic pain requires careful consideration of a variety of clinical and psychosocial factors. Using a systematic approach to combine evidence from clinical studies and expert opinion, a multidisciplinary European expert panel developed detailed recommendations to support appropriate referral and selection for SCS in chronic pain. These recommendations are available as an educational e‐health tool (https://www.scstool.org/ ).